Modelling coordinated operation of two independently owned hydro power plants in same basin : : doctoral thesis - Rajšl, Ivan (I. Rajšl ; Fakultet elektrotehnike i računarstva, 2015)
SUMMARY: Interaction of two independent owners on the same reservoir (using the same water resources) was the main driver of this research. Very few papers in recent literature deal with this problem. The main objective of the thesis was to establish a framework for the coordination of two independently owned Hydro Power Plants sharing the same reservoir. The relationship between two independent hydropower companies that use water from the same reservoir is described and a model of financial interaction between an existing Hydro Company and a new Pumped Company that owns the pumped storage hydro power plant has been proposed. In this model the shared reservoir is discretized and head effects are considered. The thesis also provides proof of a possible positive effect of new Pumped Storage Hydro Power Plant on social welfare and of negative or neutral effects of Pumped Company decisions on expected Hydro Company profit. Therefore, a mechanism compensating these negative effects of the Pumped company on the Hydro Company is introduced. The basic idea is that the compensation price signal is based on the amount of pumped water, introducing the 'water trading’ concept. Two compensation methods are proposed: uniform hourly water prices, and hourly water prices based on stochastic analysis. In both methods the shared reservoir is discretized and head effects are taken into consideration. Additionally coordination between existing Hydro Power Plant and new Pumped Storage Hydro Power Plant during spillage is proposed. Two methods are proposed for Hydro Company – Pumped Company coordination during spillage. In these two methods, a simplified model is used and head effects are neglected. Results of all mentioned methods are also presented. The MILP approach was used. Optimizations were performed using the Modelling system for mathematical programming and optimization - GAMS and simulations using programming package - Matlab. -